BİN TANRILI ZAMANLARINDA ANADOLU'DA DİN. - CENGİZ, Tülin (Turkish Culture & Haci Bektas Veli Research Quarterly, 2024)
The "Thousand Gods" period of Anatolia is the Hittite age, which took its place on the stage of history in the first quarter of the second millennium BC and created a unique religious structure. The political and cultural relations they established with many contemporary civilizations from the Aegean Sea to the Persian Gulf, from the Black Sea to Egypt were decisive in the process of creating the "thousand gods" of this ancient Anatolian civilization, which called itself the inhabitants of a country with a "thousand gods". The archaeological remains, cuneiform and hieroglyphic documents of this civilization, which was born in Anatolia and was one of the power centers of its age with its cosmopolitan structure, military and diplomatic strategies, shed light on the past. For this reason, the study of the Hittite language and culture is of great importance in understanding many aspects of today's Anatolian culture. The aim of this study is to examine the religious structure in Anatolia of the Hittite period, which created a large group of gods, from ancient Anatolian civilizations such as Hatti, Luwi and Pala to the gods of neighboring civilizations such as Sumerian, Hurrian, Assyrian and Babylon, from theology to the history of religions; to contribute to many disciplines that carry out studies on religion and belief, from cultural history to psychology of religion.